(untitled) (Revista Científica Integrada, 2025)
Menstrual poverty is a problem that is currently being widely debated. In short, it is the lack of access basic sanitation and personal hygiene items needed during the menstrual period, such as sanitary pads and toilet paper. This problem is experienced by menstruators who don’t have enough income to afford these products. Lacking them, they end up using other means to deal with the bleeding during this period, such as tissues and, in cases of greater poverty, breadcrumbs. Because of this, the federal government is studying ways to make menstruation more dignified for people on low incomes. This article aims to introduce concepts about menstruation, menstrual poverty and menstrual dignity. It points to data on menstrual poverty, as well as the measures already adopted to minimize the suffering and rescue the dignity of people in poverty who menstruate and addresses possible solutions to this problem.